2018
DOI: 10.1093/jac/dky128
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and CSF pharmacokinetics of meropenem in neonates and young infants: results from the NeoMero studies

Abstract: BackgroundSepsis and bacterial meningitis are major causes of mortality and morbidity in neonates and infants. Meropenem, a broad-spectrum antibiotic, is not licensed for use in neonates and infants below 3 months of age and sufficient information on its plasma and CSF disposition and dosing in neonates and infants is lacking.ObjectivesTo determine plasma and CSF pharmacokinetics of meropenem in neonates and young infants and the link between pharmacokinetics and clinical outcomes in babies with late-onset sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 35 publications
3
62
2
Order By: Relevance
“…Since quantitative data on membrane permeability of meropenem were not available from literature, the brain permeability parameter was obtained for the adult population by empirical optimization. The value we derived this way (0.003 L/h) is in the same order of magnitude as intercompartmental clearances that have been described in population PK models for adults and children (0.0017 and 0.0007 L/h, respectively) [17, 20]. This estimated permeability was subsequently applied in simulations with the pediatric model, which is also in accordance with studies in which a correlation between TNFα and blood-brain barrier damage was found, but not between TNFα and age [21].…”
Section: Discussionmentioning
confidence: 80%
“…Since quantitative data on membrane permeability of meropenem were not available from literature, the brain permeability parameter was obtained for the adult population by empirical optimization. The value we derived this way (0.003 L/h) is in the same order of magnitude as intercompartmental clearances that have been described in population PK models for adults and children (0.0017 and 0.0007 L/h, respectively) [17, 20]. This estimated permeability was subsequently applied in simulations with the pediatric model, which is also in accordance with studies in which a correlation between TNFα and blood-brain barrier damage was found, but not between TNFα and age [21].…”
Section: Discussionmentioning
confidence: 80%
“…Another example of nonmaturational factors for drug disposition is disease condition. As part of the NeoMero trials in neonates with late onset sepsis (NeoMero-1) and/or meningitis (NeoMero-2), Germovsek et al reported a (model-based) penetration of meropenem, a broad-spectrum carbapenem, into the cerebrospinal fluid (CSF) of 8% in neonates (Germovsek et al, 2018). This overall low value was attributed to the absence of meningeal inflammation in many of the NeoMero-1 patients without meningitis.…”
Section: Neonatal Pharmacology: Driven By Maturational and Nonmaturatmentioning
confidence: 99%
“…However, this percentage rose with increasing CSF protein, with even 40% penetration predicted at a protein concentration of 6 g/L, i.e. when inflammation of the meninges is present (Germovsek et al, 2018). For asphyxiated neonates treated with TH, both the underlying pathophysiology as well as the hypothermia treatment are considered as nonmaturational factors impacting drug disposition.…”
Section: Neonatal Pharmacology: Driven By Maturational and Nonmaturatmentioning
confidence: 99%
“…Blood and cerebrospinal fluid samples were collected for pharmacokinetic assessment; the results of this are reported separately [22].…”
Section: Plos Onementioning
confidence: 99%